Production Rate Modelling towards Salt Consumption as a Solution to Avoid Hypothyroid Disease for Indonesian People - Setyowisnu, Glagah Eskacakra; Febriawan, Muhamad Rizky; Asiyah, Ai Aas Siti; Khasanah, Nisa Uswatun; Prihantini (Proceeding International Conference on Science and Engineering, 2020)
Salt is one of the essential ingredients that is very important for all people. The use of salt has never been separated from everyday life by all corners of the world, including Indonesia. The Indonesian people's need for salt reaches a high enough number that there has never been a shortage of salt. This certainly can be a problem in meeting the basic needs of the Indonesian people and impacting on public health, iodine deficiency which causes hypothyroid disease. From this case, this study aims to model the rate of salt production with the consumption rate momentum among the people. This mathematical model is constructed from one of Newton's new laws of motion, 3rd Newton’s Law with several assumptions and ignores the human factor in production. The results of the model will be analyzed and determined the best solution to overcome the shortage of salt available in Indonesia.